Wheat production in southeast-asia - potential and constraints - Aggarwal, Pramod Kumar (SAGE Publications, 1988)
Although some wheat has in the past been grown in Southeast Asia, it is not at present a significant crop in this area. However, changing circumstances – in particular the need in some countries to diversify as a result of overproduction of rice – have led to increasing attention being directed to its possibilities. This article reviews the potential and the major constraints limiting wheat production in Southeast Asia.